A healthy eating index to measure diet quality in pregnant women in Singapore: a cross-sectional study. Issue 1 (December 2015) - Han, Chad; Colega, Marjorelee; Quah, Elaine; Chan, Yiong; Godfrey, Keith; Kwek, Kenneth; Saw, Seang-Mei; Gluckman, Peter; Chong, Yap-Seng; Chong, Mary
Abstract Background There are limited tools to assess diet quality in pregnant women in an Asian population. A healthy eating index for pregnant women in Singapore (HEI-SGP) was developed and its association with maternal characteristics examined. Methods The HEI-SGP was adapted from the Healthy Eating Indices (HEI) and Alternate Healthy Eating Index for Pregnancy (AHEI-P) and modified accordingly to recommendations from the Singapore dietary guidelines for pregnant women. It included eight components to reflect the dietary adequacy and quality of food groups and two nutrient-based components to reflect nutrients to be taken in moderation. Total scores range from 0 to 100. Study participants were from a mother-offspring cohort study – Growing Up in Singapore Towards healthy Outcomes (GUSTO), selected using criterion based sampling. Dietary intakes of these women were ascertained at 26–28 weeks of gestation using 24-hour recalls and 3-day food diaries. Results The HEI-SGP differentiated the diets qualitatively in the cohort of 955 women. The scores had a wide range of 12.6 - 94.3, with mean score of 52.4 (standard deviation 13.8) and were categorised by tertiles. Using one way ANOVA and chi-square tests, participants in the high tertile, compared to those in the middle and low tertiles, were more likely to meet recommendations for intakes of total fruits, whole fruits, total vegetables, dark green leafy and orange vegetables and dairy food groups (p < 0.001 for all). Those in the low tertile had significantly higher percentage of energy from total fat (p < 0.001) and saturated fat (p < 0.001), and lower percentage of energy from protein (p < 0.001) compared to participants from the two higher tertiles. From adjusted multinomial logistic regression analyses, women with poorer diet quality tended to be younger (odds ratio (OR) = 0.94; 95 % confidence interval (CI): 0.90-0.97), belonged to the Malay ethnic group (OR = 2.54; 95 % CI: 1.55-4.16), had lower household incomes (OR = 2.00, 95%CI: 1.03-3.87), were less educated (OR = 1.96, 95%CI: 1.19-3.25), single or had previous pregnancies (OR: 1.51; 95%CI 1.02, 2.24). Conclusions The HEI-SGP has shown to be useful for differentiating diet quality and may be used to identify women 'at risk' of poor diets during pregnancy and whom require early intervention. Clinical Trial Registry NCT01174875